Kriteria vir 'n Afrikaanse aanleerderwoordeboek - Otto, Anna Nel (Lexikos, 1999)
Criteria for an Afrikaans learner's dictionaryThis article determines the theoretical and practical criteria for an Afrikaans learner's dictionary. The target users of this dictionary is black tertiary students for whom Afrikaans is a second or third language. Such a dictionary should be directed at the needs of the target users, i.e. be a suitable medium for both decoding and encoding. The compilation of the learner's dictionary should chiefly be based upon real language use. This entails a thorough data collection which should contain adequate detail and is presented systematically. The selected information should be understandable and easily retrievable. The dictionary should have an explanatory section. The recording of macrostructural elements should be linguistically motivated. The recording of specific macrostructural elements should be based on the needs of the target users and insights of the lexicographer with regard to interlingual aspects. As far as the microstructure is concerned, adequate pronunciation, grammatical, semantic and usage guidance should be provided.